2022
DOI: 10.3390/su142114415
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma and Countermeasures of Public Interest Litigation of Marine Environmental Pollution in China

Abstract: Cases of marine environmental pollution (MEP), such as condensate leakage in the Sanchi case, not only directly infringe on private personal health and property rights, but also cause serious damage to the marine ecological environment. This paper analyzes dozens of MEP cases and summarizes the typical rights, interests, and remedies under Chinese law. Traditional tort liability legislation remedies the problem of infringement of private interests by environmental torts through compensation and punitive damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…This paper first analyses the types of cases, geographical distribution, standing, distribution of causes of action, jurisdiction, claims, adjudication, and other elements in 339 cases of MEPIL. Based on the analysis, it is found that China's MEPIL has distinctive characteristics (Jia, 2022) and is designed to protect public interests such as marine ecology and biological resource diversity (Li, 2022), effectively enforces the law (Liu Z., 2020) and enhance sustainable development (Zhai, 2018). In addition, China's MEPIL faces obstacles such as a low record of lawsuits filed by administrative organs, inadequate legal basis for standing of social organizations, under-utilization of the ecological damage compensation (Xie and Xu, 2021), and the defects of the litigation jurisdiction system (Xie and Xu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This paper first analyses the types of cases, geographical distribution, standing, distribution of causes of action, jurisdiction, claims, adjudication, and other elements in 339 cases of MEPIL. Based on the analysis, it is found that China's MEPIL has distinctive characteristics (Jia, 2022) and is designed to protect public interests such as marine ecology and biological resource diversity (Li, 2022), effectively enforces the law (Liu Z., 2020) and enhance sustainable development (Zhai, 2018). In addition, China's MEPIL faces obstacles such as a low record of lawsuits filed by administrative organs, inadequate legal basis for standing of social organizations, under-utilization of the ecological damage compensation (Xie and Xu, 2021), and the defects of the litigation jurisdiction system (Xie and Xu, 2022).…”
Section: Introductionmentioning
confidence: 99%